Dichlorido{4-cyclohexyl-1-[1-(2-pyridyl-kappa N)ethylidene]thiosemicarbazidato-kappa N-2(1),S}methyltin(IV) - Salam, M.A.; Abu Affan, M.; Shamsuddin, M.; Ng, S.W. (International Union of Crystallography, 2010)
The monodeprotonated Schiff base ligand in the title compound, [Sn(CH3)(C14H19N4S)Cl-2], N,N',S-chelates to the Sn atom, which is six-coordinated in an octahedral environment. The three coordinating atoms along with the methyl C atom comprise a square plane, above and below which are positioned the Cl atoms. The amino group is a hydrogen-bond donor to a Cl atom of an adjacent molecule, the hydrogen bond giving rise to a helical chain extending parallel to [100].